Memorandum az Egyetemi Levéltár szükségességéről: Kivonat a Magyar Felsőoktatási Levéltári Szövetség konferencia előadásaiból (2008–2012) - Juha, Enikő (Gerundium, 2018)
MEMORANDUM FOR THE NECESSITY OF THE UNIVERSITY ARCHIVE: EXTRACTS FROM THE PRESENTATIONS AT THE CONFERENCES OF THE ASSOCIATION OF THE HUNGARIAN HIGHER EDUCATION ARCHIVES (2008–2012). he author reported on the development of the documents during the history of the University of Debrecen at several conferences, emphasizing the fact that among all the Hungarian higher education institutions, the one in Debrecen has no separate archive. After a short retrospect, the present status of the document management at the University of Debrecen is introduced showing an odd picture of the situation since the doscument collections, although following the rules of the archive maintenance, are still scattered in separate locations. Parts of the collectionscan be found in the Hajdú-Bihar County Archive, in the Central Archive and in the University Library. he review written in favour of a uniied archive introduces the main subject units of the collections.